Towards Modern Aesthetics: Charlotte Brontë and J. M. W. Turner*. (3rd April 2018) - Choe, Jian
Abstract : This article aims to consider the intersections between Charlotte Brontë and William Turner, as shown in their text and image, centring upon the ways in which they worked towards the style that would be called impressionism. This particular aesthetic can clarify all the major dimensions of their mature art: epistemological, technical and even thematic. Their artistic careers coincided with a period of great social change and their innovative art was forged in response to the shifting conditions of their time. They witnessed the advent of the modern world, attempting to give form to the new mode of existence and consciousness. An inquiry into the parallels between the two eminent Victorians suggests that they carved out an aesthetic of modernity, which laid the foundation for the future course of art and literature.